2017
DOI: 10.18869/acadpub.jafm.73.241.26529
|View full text |Cite
|
Sign up to set email alerts
|

Maximum Smoke Temperature in Non-Smoke Model Evacuation Region for Semi-Transverse Tunnel Fire

Abstract: Smoke temperature distribution in non-smoke evacuation under different mechanical smoke exhaust rates of semi-transverse tunnel fire were studied by FDS numerical simulation in this paper. The effect of fire heat release rate (10MW 20MW and 30MW) and exhaust rate (from 0 to 160m 3 /s) on the maximum smoke temperature in non-smoke evacuation region was discussed. Results show that the maximum smoke temperature in non-smoke evacuation region decreased with smoke exhaust rate. Plug-holing was observed below the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Once the tunnel catches fire, the high-temperature smoke generated by the fire will reduce the visibility of the tunnel and increase the difficulty of evacuation. Therefore, a well-designed ventilation system mainly includes mechanical ventilation (longitudinal ventilation [1] , transverse ventilation [2] , semi-transverse ventilation [3] ) system and natural ventilation system, which can ensure the safety of trapped persons. The mechanical ventilation system is less affected by the external environment and has high stability.…”
Section: Intruductionmentioning
confidence: 99%
“…Once the tunnel catches fire, the high-temperature smoke generated by the fire will reduce the visibility of the tunnel and increase the difficulty of evacuation. Therefore, a well-designed ventilation system mainly includes mechanical ventilation (longitudinal ventilation [1] , transverse ventilation [2] , semi-transverse ventilation [3] ) system and natural ventilation system, which can ensure the safety of trapped persons. The mechanical ventilation system is less affected by the external environment and has high stability.…”
Section: Intruductionmentioning
confidence: 99%
“…Evacuation efforts are impeded, and survival chances are reduced by high temperature and smoke, exacerbating the danger of tunnel fire. 3 To inhibit the burning of asphalt during a tunnel fire, effective flame-retarding measures are taken on asphalt materials. Usually, a flame retardant is incorporated into asphalt pavements to delay asphalt burning.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Formaldehyde solution (37 wt % in H 2 O) is a colorless and pungent liquid. Its density at 25 °C is 1.09 g/cm 3 , melting point −15 °C, and boiling point 95 °C. Anhydrous sodium carbonate is a white powder with a purity superior to 99.5%.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For example, Lou et al investigated the effects of the heat release rates of fire (10,20,and 30 MW) and exhaust rate (from 0 to 160 m3/h) on the maximum gas temperature in tunnels. They found that the maximum gas temperature rise at tunnel vault is proportional to ¾ power of non-dimensional heat release rate of fire (Lou et al 2017). Li et al analytically and experimentally investigated the maximum temperature of buoyant gases beneath the tunnel ceiling in presence of fire and found that the heat release rate and the tunnel inlet velocity play important rules in the maximum ceiling gas temperature (Li and Ingason 2012;Li et al 2011).…”
Section: Introductionmentioning
confidence: 99%